Rice farming systems in Southern Lao PDR: Interpreting farmers' agricultural production decisions using Q methodology. (February 2018) - Alexander, Kim S.; Parry, Lucy; Thammavong, Phomma; Sacklokham, Silinthone; Pasouvang, Somphanh; Connell, John G.; Jovanovic, Tom; Moglia, Magnus; Larson, Silva; Case, Peter
Abstract: The agricultural sector in Lao PDR is forecast to move from subsistence rice production to a more modernized and market-oriented sector with greater focus on commercialization of agricultural production. Intensification of agricultural production in the southern and central rice growing regions of Lao PDR is problematic as dryland farmers rely on rainfall and soils are poor, yet rural households have been experiencing rapid change in their farming and livelihood systems. This paper employs Q methodology techniques to explore 35 farmers' viewpoints when contemplating their production goals and potential to adopt technologies to improve productivity. Findings describe the two emerging viewpoints among farmers as 'labour saving productivity maximization' and 'traditional labour productivity using improved techniques'. The two viewpoints describe the different issues currently guiding production decisions. While the Lao Government forecasts substantial increases in rice production in the southern plains, farmers will require specialized and tailored support, accounting for their envisaged livelihood and production goals, to allow the sector transformation that many stakeholders currently envisage. Highlights: Visual Q methodology techniques have been used to explore Lao rice farmers' attitudes to productivity and introduced technologies. Lao farmers' production decisions are based on labour requirements; production activities are viewed as 'labour saving ' or ' traditional labour '. Farmers require specialized support, tailored to their livelihood and production goals to improve productivity. Stakeholders should shift focus from preoccupations with introduced technologies towards users' dispositions, perceptions and preferences.